Diet high in fructose promotes liver steatosis and hepatocyte apoptosis in C57BL/6J female mice: Role of disturbed lipid homeostasis and increased oxidative stress. (May 2017) - Choi, Youngshim; Abdelmegeed, Mohamed A.; Song, Byoung-Joon
Abstract: The effects of high (H)-fructose (FR) diet (D) (HFRD) on hepatic lipid homeostasis, oxidative stress, inflammation and hepatocyte apoptosis were investigated in 6-week old female C57BL/6J mice fed a regular chow (ContD) or HFRD (35% fructose-derived calories) for 3 weeks. HFRD-fed mice exhibited increased levels of hepatic steatosis with a significant elevation of serum levels of triglyceride, cholesterol and TNFα compared to ContD-fed mice (P<0.05). HFRD-fed mice exhibited ∼2.7- fold higher levels FAS along with significantly decreased protein levels of adiponection-R2 (∼30%), P-AMPK (∼60%), P-ACC (∼70%) and RXR-α (∼55%), suggesting decreased hepatic fat oxidation compared to controls. Interestingly, hepatic fatty acid uptake into hepatocytes and lipolysis were significantly increased in HFRD-fed mice, as shown by decreased CD36 and fatty acid transporter protein-2, and increased adipose triglyceride lipase, respectively (P<0.05). Increased hepatic levels of iNOS and GSSG/GSH suggest elevated oxidative stress with a higher number of macrophages in the adipose tissue in HFRD-fed mice (P<0.05). Significantly elevated rates of hepatocyte apoptosis (∼2.4-fold), as determined by TUNEL analysis with increased Bax/Bcl2 ratio and PARP-1 levels (∼2- and 1.5-fold, respectively), were observed in HFRD-fed mice. Thus, HFRD exposure increased hepatic steatosis accompanied by oxidative stress and inflammation, leading to hepatocyte apoptosis. Graphical abstract: Highlights: HFRD-fed mice exhibited higher levels of hepatic lipogenesis as evidenced by increased FAS and SCD1. Hepatic fatty acid oxidation was inhibited as evidenced by decreased adiponection-R2, P-AMPK, P-ACC, and RXR-α. HFRD increased the hepatic levels of iNOS and GSSG/GSH, suggesting the development of oxidative stress. HFRD-fed mice elevated the levels of macrophages and pro-inflammatory cytokine TNF-α in the adipose tissue. HFRD-fed mice exhibited increased hepatocyte apoptosis, as shown by the elevated levels of Bax/Bcl2 ratio and PARP-1 protein.